2022
DOI: 10.3390/separations9080204
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and Proteomic Profile of Dried Hop Inflorescences (Humulus lupulus L. cv. Chinook and cv. Cascade) by SPME-GC-MS and UPLC-MS-MS

Abstract: Hop (Humulus lupulus L.) is grown mainly for the production of beer. The flowers of the female plant give it the bitter taste and pungent aroma. There are a large number of hop varieties differing in their α-acid content, essential oil levels and odor profiles. Aside from their use in brewing, more recently, hops have been used for the pharmacological properties of its derivatives that are of great importance to the pharmaceutical industry. Hop is known to have a fairly complex chemistry characterized by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…With PTR-ToF-MS, it is possible to obtain in real time the whole volatile spectrum (including low-molecular-weight compounds) with high sensitivity and high time resolution, although some compounds are ambiguously identified [10][11][12]. On the other hand, the SPME technique, although its limitation is linked to the displacement effect of analytes with a lower affinity with the type of used fiber, is ideal for MS applications as it combines simple and efficient sample preparation with versatile and sensitive detection [13,14]. Therefore, using a combined approach, the present study represents a first step towards a better comprehension of the molecular composition of cannabis pollen.…”
Section: Discussionmentioning
confidence: 99%
“…With PTR-ToF-MS, it is possible to obtain in real time the whole volatile spectrum (including low-molecular-weight compounds) with high sensitivity and high time resolution, although some compounds are ambiguously identified [10][11][12]. On the other hand, the SPME technique, although its limitation is linked to the displacement effect of analytes with a lower affinity with the type of used fiber, is ideal for MS applications as it combines simple and efficient sample preparation with versatile and sensitive detection [13,14]. Therefore, using a combined approach, the present study represents a first step towards a better comprehension of the molecular composition of cannabis pollen.…”
Section: Discussionmentioning
confidence: 99%
“…113 In general, the proteomics of hops is partly revealed. 114 Even so, targeted experimental studies on hop proteins in beer to investigate mousy off-flavor development and mitigation strategies are needed. Hence, understanding the total amino acids and specifically the amino acid profile would help brewers understand the risks of amino acid derived off-flavors.…”
Section: Proteins and Amino Acids In Beer Matrixmentioning
confidence: 99%
“…Humulinone has several sites from which can bind to protein Z, including Asn-37, Ser-292, Lys-290, and Pro-395, and it can be introduced to beer through dry hopping, which results in a decrease in soluble protein content or free amino nitrogen content. , However, free amino nitrogen content measured in sweet, hopped, and unhopped wort suggested that nitrogen increases after the hopping procedure . In general, the proteomics of hops is partly revealed . Even so, targeted experimental studies on hop proteins in beer to investigate mousy off-flavor development and mitigation strategies are needed.…”
Section: Proteins and Amino Acids In Beer Matrixmentioning
confidence: 99%
“…In a recent study, Nezi et al (2022) reported the percentage distribution of different protein classes found in hop cones from Cascade and Chinook varieties grown in southern Italy [92]. The most abundant was the class related to photosystems (19%), followed by those related to ATP synthase and flavonoid pathways.…”
Section: Chemical Composition Of H Lupulusmentioning
confidence: 99%